Case report - sulfonylurea poisoning mimicking vertebrobasilar acute ischemic stroke - Kędra, Kamila; Michalik, Izabela; Oleszko, Michał; Wiącek, Marcin (Journal of Education, Health and Sport, 2023)
Background: We report the case of sulfonylurea induced hypoglycemia manifesting as acute encephalopathy with focal neurological signs misdiagnosed as posterior circulation acute ischemic stroke (AIS) and discuss the potential effects of hypoglycemia on central nervous system, as well as its differentiation from AIS. Case presentation: A 64-year-old patient with type II diabetes treated with glimepiride was transferred to the Department of Neurology after the procedure of radical prostatectomy. On admission, the patient was unconscious with four limb paresis and bilateral Babinski sign. Non-contrast head CT and CT angiography vessels did not reveal any abnormalities. Due to exceeded therapeutic window the patient was disqualified from intravenous thrombolysis. At the admission hypoglycemia was observed and promptly corrected with the 5% dextrose infusion. For the next 72 hours repeated intravenous glucose infusions were needed to maintain its levels above 70 mg/dl. Based on the absence of ischemic changes on MRI and repeated decreases in glucose level for the next 3 days, glimepiride induced hypoglycemic encephalopathy was diagnosed. Within 24 hours of admission the patient regained consciousness and eventually presented four-limb paresis as a result of prolonged neuroglycopenia. Conclusions: Prolonged insufficient brain nutrition can result in permanent or long-lasting brain damage, manifesting as impaired consciousness and focal neurological signs. Perioperative sulfonylureas intake may result in prolonged hypoglycemia.